Persepsi guru terhadap penggunaan aplikasi Anates DI SMA - Putra, Gandi Novis; Sesmiyanti; Siska (EduCurio: Education Curiosity, 2023)
This study aims to determine the teacher's perception of the use of the Anates application at SMA PGRI 03 Padang. This research was conducted using a descriptive through a qualitative approach. For data collection, researchers used interviews as a research instrument, researchers interviewed teachers with audio recording devices. The participant of this study was an English teacher at SMA PGRI 03 Padang as the source for the interview. The results of this study indicate that teachers find this application very useful for evaluating the results of student answer sheets. In addition, researchers also found that teachers feel comfortable when using the Anates application, because it is very helpful in the process of evaluating the results of student answer sheets. However, the researcher also found that teachers felt that the Anates application was still not effective in weighting essay questions. Overall, teachers find it helpful in using the Anates application.